Financial sector reforms and economic growth in Ghana: A dynamic ARDL model - Erasmus L. Owusu; Nicholas M. Odhiambo (Contemporary Economics, 2015)
This paper examines the relationship between financial sector reforms and sustainable economic growth in Ghana. Employing the autoregressive distributed lag (ARDL) bounds testing approach and using GDP per capita as a growth indicator, this paper establishes a long-run relationship between economic growth and financial reforms, which is represented by an index calculated using principal component analysis (PCA). The paper finds that in the long run, financial sector reforms have an insignificant impact on economic growth in Ghana. This supports numerous past studies that have reported mixed or inconclusive results on the effects of financial reforms on economic growth. The paper concludes that increase in capital stock, not financial sector policy reforms, affects economic growth in Ghana. This paper therefore recommends an increase and modernization of capital stock in order to promote real sector growth in Ghana.
Keywords: C32; G12; O16; O47; 330; Africa; Ghana; Economic Growth; Financial Sector Reforms; ARDL Bounds Testing Approach